CODIFICATION OF AFRICAN MUSIC AND TEXTBOOK PROJECT: A PRIMER OF PRACTICAL SUGGESTIONS FOR FIELD RESEARCH, by Hugh T. Tracey with Gerhard Kubik and Andrew T. N. Tracey (International Library of African Music, 1969). 54 pp. - Pantaleoni, Hewitt (International Library of African Music, 1971)
pages: 95-98
Keywords: African Music